Valuing patient engagement: Reflexive learning in evidence generation practices for health technology assessment. (July 2021) - Gunn, Callum J.; Bertelsen, Neil; Regeer, Barbara J.; Schuitmaker-Warnaar, Tjerk Jan
Abstract: Much attention in health technology assessment (HTA), a health system governance mechanism used for determining the value of health technologies, is being paid to improving the quality and patient-relevance of the evidence used in assessment pratices. Whilst the direct involvement of patient actors throughout HTA processes has become a more routine element of institutional practice, the 'impacts' of patient engagement (PE) initiatives have proven difficult to determine and enhance. In reflexive governance theories, reflexive learning is a critical mechanism of multi-stakeholder arrangements that better handles the complexities of technologies and how they are understood through governance practices. This paper explores how reflexive learning can be used to build a richer conceptualisation of PE in HTA, in order to generate suggestions for enhancing PE practices and their impact. We critically apply reflexive learning insights on qualitative data derived from the co-creation process of a PE evaluation framework, organised through an EU project focused on strengthening PE practices across medicines development (2018–2020), including 24 interactive case studies, 3 multi-stakeholder workshops, and our observations throughout the project. The findings characterise two dimensions of reflexive learning in PE: First, reflexive learning refers to the adaptive reorganisation of evidence generating practices, including the revision of medicines' evaluation criteria and the conditions under which evidence 'relevant' to HTA is constructed. Second, reflexive learning spotlights the sociopolitics which shape technology evaluation. Four themes affecting meaningful and sustained PE in medicines development were analysed: institutional boundaries due to established evaluation criteria; timing of engagements; network relations between institutional actors; and the politics of patient representation. Extending beyond discrete PE activities and their reported impacts, reflexive forms of learning are crucial to yielding more 'meaningful' PE for HTA and medicines development, facilitating a HTA practice that more meaningfully deals with the complexities of medicines evidence generation. Highlights: Approaches the value of patient engagement (PE) to Health Technology Assessment (HTA). Analyses qualitative data from EU project on PE evaluation in medicines development. Conceptualises PE practices with reflexive learning. Reflexive learning affords a richer understanding PE's value or impact. Reflexive forms of learning needed for meaningful PE in developing evidence for HTA.